2014
DOI: 10.1248/bpb.b14-00281
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Ameliorates Hepatic Steatosis and Fibrosis by Down-Regulating SREBP1 Gene Expression <i>via</i> AMPK-mTOR-p70S6K Signaling Pathway

Abstract: Beneficial effect of eugenol on fatty liver was examined in hepatocytes and liver tissue of high fat diet (HFD)-fed C57BL/6J mice. To induce a fatty liver, palmitic acid or isolated hepatocytes from HFD-fed Sprague-Dawley (SD) rats were used in vitro studies, and C57BL/6J mice were fed HFD for 10 weeks. Lipid contents were markedly decreased when hepatocytes were treated with eugenol for up to 24 h. Gene expressions of sterol regulatory element binding protein 1 (SREBP1) and its target enzymes were suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 27 publications
2
24
4
3
Order By: Relevance
“…In addition, suppressing the activation of P70S6K, a key downstream kinase of mTOR, can promote autophagy (Sun et al, 2018a). It has been shown that eugenol activates AMPK phosphorylation, but suppresses mTOR and P70S6K phosphorylation, which attenuates hepatic steatosis and fibrosis (Jo et al, 2014). In the present study, the ratio of p-AMPKa/ AMPKa was increased, while p-mTOR/mTOR and p-P70S6K/ P70S6K ratios were reduced by MCAO or OGD/R, which was further strengthened by eugenol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, suppressing the activation of P70S6K, a key downstream kinase of mTOR, can promote autophagy (Sun et al, 2018a). It has been shown that eugenol activates AMPK phosphorylation, but suppresses mTOR and P70S6K phosphorylation, which attenuates hepatic steatosis and fibrosis (Jo et al, 2014). In the present study, the ratio of p-AMPKa/ AMPKa was increased, while p-mTOR/mTOR and p-P70S6K/ P70S6K ratios were reduced by MCAO or OGD/R, which was further strengthened by eugenol.…”
Section: Discussionmentioning
confidence: 99%
“…SREBP1 binds to the sterol regulatory element in the nucleus, and activates the transcription of target genes, such as Fasn, Elvol6 and Scd1, associated with fatty acid synthesis (Xu et al, 2016). Several studies indicated that the lipid accumulation was caused by modulating the activation of SREBP1 signaling in hepatocytes isolated from HFD-fed rodent (Jung et al, 2012;Jo et al, 2014;Kim et al, 2019). Therefore, suggesting that HFD feeding might induce de novo lipogenesis via the activation of SREBP1 signaling in the sciatic nerves similar to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK was shown to phosphorylate SREBP1c at Ser372, suppressing the proteolytic cleavage of precursor SREBP1c into mature SREBP1c, leading to the suppression of hepatic steatosis in diet-induced insulin-resistant mice. 56) In addition to direct regulation, AMPK can further reduce hepatic lipid contents by suppressing SREBP1c expression through decreasing the activity of mammalian target of rapamycin complex (mTORC), 57,58) an important mediator for the regulation of cellular metabolism and growth that may also promote SREBP-dependent fatty acid synthesis. mTORC1-dependent activation of SREBP1c is thought to accelerate fatty acid synthesis by cleavage of the SREBP1c molecule.…”
Section: Ampk-mediated Regulation Of Proteins Involved In Lipid Metabmentioning
confidence: 99%